Metropolitan Andrei Sheptytskyi - environmental representative of Halychyna - Haydukevych, Olena (Skhid, 2016)
The article elucidates important aspect of Metropolitan Andrei Sheptytskyi’s diversified activity - environmental protection in Halychyna. The author proves that Metropolitan’s environmental activity was aimed at the intensification of national revival in the region. It was important for the consolidation of Halychian’s self-respect and steady growth of their spiritual worldview. The article suggests various archival documents that contain facts of Metropolitan’s environmental activity in Halychyna in 1930-1940. Metropolitan Andrei always pays great attention to environmental protection and conservation activities fully support the various segments of the Ukrainian community of Galicia. The main stages of this activity - an organization in Gorgan, near the village. Osmoloda on the lands of the first Ukrainian Church Cedar Reserve, which later was given the name of Metropolitan Andrei Sheptytskyi First National Park Nature Nature Reserve "Devil’s Mountain" near. Rohatyn, "Cash Mountain" near the village. Bovše in the vicinity. Galich, forests estates "Zarvanytsya" Podgaetskiy county in the region, protection of some old, old trees as monuments of nature, a number of other events, which, though indirectly, however, contributed to conservation land (attempt open in Lviv Ukrainian University, purchase 4 thousand. hectares of forest near the village. Yanov, on the basis of which it was established the Institute "forest Foundation Lviv Greek Catholic eparchy" which included testing Yaniv forestry and forest research station, is the financial support of the National museum in Lviv care about the economic activity of the Ukrainian Academy in Podebrady (Czech Republic), gift of the land area of 50 mortuaries with a large garden and a garden in the village. Mylovannya society "Enlightenment," which became the basis for local school field crops, etc.). Nature and the environment as an important aspect of the Metropolitan, was aimed at strengthening of national revival in the land, had considerable importance for establishing national dignity Galicians approached their nature, sowed grains of environmental ideas as a way to increase national, religious and moral consciousness people is through steady expansion of its spiritual world, strengthening economic situation and increasing material prosperity, based on lies and love for his native land and native wildlife.